Attitude Of Employed Mothers and Housewives Toward Family Physicians in Primary Health Care Centers - Salih Ismael, Nibras; Hussein Kadhim, Shahad (South Asian Journal of Social Sciences and Humanities, 2025)
Aim of study: To evaluate the attitude of Employed mothers and housewives toward family  physicians in primary health centers and to identify the general satisfaction of participants with the services provided by Family physicians. Method: A cross-sectional study was conducted  in 4 primary health care centers in Baghdad (AL-Resafah sector, AL-Karikh sector), period  from 1st of January 2019 to 1st of June 2019. Sample of a study from a mother who attending  the PHCC who have multiple visits, information was obtained by interviewing participants and  data entry and analysis was done by using (SPSS-24) then categorized into tables and figures.  Result: A total of 250 participants included in this study, the most common age groups was 25-45 years. 62% were married and the rest were either widow or divorced. 72.8% were living in  urban area and the rest 27.2% were from rural area. Nearly half of participants were Employed,  112(44.8%) of participants they prefer physicians' age≥45y, 128(51.2%) of participants they  have no difference for preferring physicians' gender. Conclusion: More than half of participants  have good attitude toward family physician. There was no statistically significant difference  with some of participants' characteristics and satisfaction level. Some of participants showed  dissatisfaction with the appointment for the next visit and more than half showed dissatisfaction  with the waiting time.
Keywords: Attitude; Employed mothers; housewives; family physician; primary health centers